CYTOKINE PROFILE IN PATIENTS USING REMOVABLE PARTIAL DENTURE OF DIFFERENT BASIS MATERIAL - Schulzhenko, O.Y.; Silenko, Y.I.; Mamontova, T.V.; Kalashnikov, D.V. (World of Medicine and Biology, 2013)
The results of investigation of proinflammatory cytokine TNF-α and antiinflammatory cytokine IL-10 in oral liquid of patients using removable partial denture of different basis material are presented. It was shown that presence denture with carcass of metal and thermoplasts contribute to more effective restoration of balance pro-/anti-inflammatory cytokines and adaptation of prothesis couch tissues to removable partial denture.
Keywords: removable partial denture; cytokine profile